Reproductive Outcomes in Young Breast Cancer Survivors Treated (15–39) in Ontario, Canada - Moira Rushton; Jessica Pudwell; Xuejiao Wei; Madeleine Powell; Harriet Richardson; Maria P. Velez (Current Oncology, 2022)
We conducted a population-based, retrospective, matched-cohort study to examine the impact of breast cancer diagnosis and treatment on fertility outcomes. Relative risks of infertility, childbirth, premature ovarian insufficiency (POI; age < 40) and early menopause (age < 45) were calculated using modified Poisson regression. Our primary cohort included young women (15–39) with early stage BC diagnosed 1995–2014. Five cancer-free patients were matched to each BC patient by birth year and census subdivision. The BC cohort was further divided by treatment with chemotherapy vs. no chemotherapy treatment. 3903 BC patients and 19,515 cancer-free women. BC patients treated with chemotherapy were at increased risk of infertility (RR 1.81; 95% CI 1.60–2.04), and POI (RR 6.25; 95% CI 5.15–7.58) and decreased childbirth (RR 0.85; 95% CI 0.75–0.96), compared to women without cancer. BC patients who did not receive chemotherapy were also at increased risk of infertility (RR 1.80 95% CI 1.48–2.18) and POI (RR 2.12 95% CI 1.37–3.28). All young BC survivors face an increased risk of diagnosed infertility and POI relative to women without cancer, independent of chemotherapy. These results emphasize the importance of pre-treatment fertility counselling for young women diagnosed with BC.